Sintesis dan Karakterisasi Magnetik Kuantum Dot Fe3O4 Dengan Metode Kopresipitasi - Hamid, Abdul; Isnaeni, Isnaeni; Amran, Ali; Beri, Deski (Periodic, 2024)
The unique properties of the magnetic quantum dot Fe3O4 make it widely synthesized by different methods and applied in the biomedical field. The synthesis method plays an important role in determining the optical properties of the magnetic quantum dot Fe3O4. This study aims to determine the magnetic synthesis of quantum dot Fe3O4 coated with oleic acid by coprecipitation method. Quantum dot Fe3O4 magnetic synthesis method by coprecipitation using oleic acid for functionalization of Fe3O4 quantum dot magnetic. The results of the FTIR analysis showed five main absorption bands namely O-H, C-H, C=C, C-O, and Fe-O which indicated that the magnetic quantum dot Fe3O4 was successfully functionalized with oleic acid.